Fentanyl inhibits the progression of human gastric carcinoma MGC-803 cells by modulating NF-κB-dependent gene expression in vivo - HE, GUODONG (Oncol Lett, 2016)
Fentanyl is widely used to treat acute and chronic pain. Previous in vitro studies by the present authors demonstrated that fentanyl inhibits the progression of the MGC-803 human gastric carcinoma cell line by affecting apoptosis-related genes, including nuclear factor-kappa B (NF-κB) and phosphatase and tensin homolog. In the present study, the effects of fentanyl on NF-κB-dependent gene expression were investigated in vivo. Nude mice were inoculated with an MGC-803 cell suspension, and mice that developed subcutaneous tumors measuring >1.0×1.0 cm were selected for study. Mice were administered intraperitoneal injections of fentanyl (0.05 mg/kg, group F1; 0.1 mg/kg, group F2; 0.2 mg/kg, group F3; and 0.4 mg/kg, group F4) for 14 consecutive days. Non-fentanyl-treated mice (group C) and normal saline-treated mice (group N) served as the control groups. Tumor growth was monitored by calculating the time-shift of the growth curve. Morphological changes were also observed using microscopy. The expression of NF-κB, B-cell lymphoma-2 (Bcl-2), B-cell associated X protein (Bax), vascular endothelial growth factor-A (VEGF-A) and matrix metalloproteinase-9 (MMP-9) in the subcutaneous tumor tissue was also analyzed by reverse transcription-polymerase chain reaction and western blot analysis, and confirmed using immunohistochemistry. The relative tumor volumes of groups F1, F2, F3 and F4 were significantly reduced compared with groups C and N. Furthermore, subcutaneous tumor cells exhibited nuclear swelling, chromatin condensation, reduced chromatin and nuclear fragmentation in the F1, F2, F3 and F4 groups. The number of NF-κB(+), Bcl-2(+), VEGF-A(+) and MMP-9(+) subcutaneous tumor cells was reduced, whereas the number of Bax(+) cells was increased in the F1, F2, F3 and F4 groups. Additionally, in these groups, tumor expression of NF-κB, Bcl-2, VEGF-A and MMP-9 transcripts and proteins was downregulated, while Bax messenger RNA and protein expression levels were upregulated. The results revealed that fentanyl inhibits the growth of subcutaneous human gastric carcinoma tumors in mice. Therefore, it could be hypothesized that this antineoplastic activity may result from the inhibition of NF-κB activation, suppression of downstream VEGF-A and MMP-9 expression, and normalization of the pro-apoptotic Bax/Bcl-2 ratio.